Anisotropic optical behavior of an amorphous organic polymer locally aligned by inkjet-printing - Lindberg, Frida; Synnatschke, Kevin; Rödlmeier, Tobias; Brenner, Philipp; Krings, Maximilian; Dietl, Martin C.; Lemmer, Uli; Backes, Claudia; Hernandez-Sosa, Gerardo (Progress in organic coatings, 2021)
The molecular arrangement of polymeric organic semiconductors alter the macroscopic optoelectronic properties of the material. Most existing solution-based deposition methods are however, limited in both resolution as well as pattern design and often result in molecular disorder upon drying. Here, a method for aligning the amorphous polymer polyindenofluoren-8-triarylamine (PIF8-TAA) via inkjet printing is presented. By tuning the printing speed and including different amounts of the solid solvent crystallization agent 1,3,5-trichlorobenzene (TCB), fibrous structures with varying morphology can be fabricated. The resulting optical properties are analyzed using photoluminescence and Raman spectroscopy. The findings show an optical anisotropic behavior dependent on the fiber size and alignment. This is likely caused by the increased molecular arrangement within the structures. Methods enabling tailored structuring of the molecular arrangement in a material, provide the possibility to develop novel applications, as well as to optimize existing devices with improved properties such as, charge carrier transport and emission efficiency.